Kinetic and kinematic analysis of three different execution modes of stag leap with and without throw- catch ball in rhythmic gymnastics - Akkari-Ghazouani, H.; Mkaouer, B.; Amara, S.; Chtara, M. (Science of Gymnastics Journal, 2020)
Visual analysis of rhythmic gymnastics shows that the greatest difficulty lies in jumps. Performing jump with optimal speed, great amplitude, and better coordination and without any mistakes, does not depend only on the gymnast's capacity but also on the apparatus used, the jump made and the applied momentum. The objective was to study the qualities of strength, speed and flexibility developed during the three execution modes of stag leap with ring with and without throw-catch ball. Seven gymnasts from the national rhythmic gymnastics team aged between 15 to 21 years participated in this study. The protocol in making three stag leaps with rings consist of the following: the first without apparatus, the second with throwing ball during the chasse step, and the third with throwing ball at the time of pulse during stag leap with ring. The basic descriptive parameters and statistical significance of differences were determined by using the SPSS 20.0, statistical program for data processing. The results show a significant variation at p <0.05 in the execution factors when introducing apparatus such as, horizontal and vertical velocity, right knee angle, force, horizontal displacement of toe, the angular momentum of the centre of mass and angular velocity of right leg. This decrease differs according to the moment of throwing the ball. In conclusion, we can argue that introducing ball during the chasse step causes a change in the basic performance factors.